Educational Leadership - Şenol, Hülya (IntechOpen, 2020)
There is a growing realization that the role of educational leaders has been undergoing many changes in the era of globalization due to the diverse needs and expectations of the stakeholders of education. Schools have different specific needs due to their demographical structure, the academic achievement level of students, the experience of teachers and parental involvement and they need educational leaders who can transform and develop schools. This book intends to provide the reader with a comprehensive overview of the expected responsibilities and features of school leaders in the context of the different models of educational leadership. Scholars from different countries share their opinions about the challenges faced by the school leaders as principals, teachers, students, school committees, and boards in schools; the importance of leader preparation and the need for the professional development of educational leaders.